Sombra comunista ou novas realidades? análise sobre o desenvolvimento da Arquivologia russa na era pós-soviética (1991-2016) - SANTOS JUNIOR, Roberto Lopes dos (Universidade Federal do Pará, 2019)
Historical analysis - based on literature and bibliographic review - identifying the main characteristics about the Russian Archival Science in the decades of the country's transition to capitalism. The period of analysis is between the second half of 1991, with the dissolution of the USSR, to 2016, on the Vladimir Putin’s Government. The article is divided in three parts: analysis about the infrastructure of the archives in post-soviet Russia and the professional formation of Russian archivists, discussion about the laws and regulations produced in the 1990s and 2000s, and the complex situation of the accessibility in Russian archives, especially for occidental researchers and users. This research identifies that, despite some problems inherited from the communist era, the archives in Russia, including the professional formation and legal structure, was open to a new horizon, adapting, partially, to the capitalist reality.